Students' emergency fund / Azlina Ahmad (Datin) - Ahmad, Azlina (Faculty of Information Technology and Quantitative Sciences, 1997)
ITM's Students' Emergency Fund had its beginnings in 1979, replacing the Group Insurance Scheme implemented since 1976. This paper begins with a brief historical perspective of the death and disability benefits given to students. This is followed by a short actuarial analysis of the current fund of the Shah Alam campus based on accounting records of 1991 through 1994. Loss ratios, an indicator of sufficiency of funds is then calculated.